The Facebook Revolution: An Exploratory Analysis of Public Pages during the Arab Political Unrest - Khashman, Nouf (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Social network sites have been viewed as viable tools for communication during the political unrest in the Arab world since it started in December 2010. This study employs content analysis method to explore the characteristics of public political Facebook pages in Tunisia, Egypt, Libya and Syria during their recent political events. Les sites de réseautage social ont été perçus comme des outils de communication viables lors de la crise politique dans les pays arabes depuis leur commencement en décembre 2010. Cette étude utilise l’analyse de contenu pour explorer les caractéristiques des pages Facebook politiques publiques en Tunisie, en Égypte, en Libye et en Syrie lors des récents événements politiques.